Acute limb ischemia in patients after myocardial infarction - Alexander, Nick; Sudargo, Giovanni Kurniawan; Setiadi, Tiya (International Journal of Research in Medical Sciences, 2022)
Acute limb ischemia is a sudden onset lower extremity emergency that threatens tissue viability and usually occurs within 14 days of symptom onset. Acute limb ischemia is one of the complications of myocardial infarction. In this case, a 54-year-old male patient came to the ER with the chief complaint of shortness of breath 30 minutes before going to the hospital, accompanied by cold sweat and nausea. The patient was diagnosed with acute pulmonary oedema, non-ST elevation myocardial infarction (NSTEMI), hypertensive heart disease with diastolic dysfunction, heart failure with decreased ejection fraction and type 2 diabetes mellitus. On the 6th day of treatment, the patient complained of right leg pain accompanied by coldness and difficulty moving. The patient was diagnosed with acute limb ischemia. This patient did not undergo endovascular revascularization surgery due to limited facilities and experts. The patient was given pharmacological therapy and the complaints improved. Therefore, it is important to be able to identify acute limb ischemia and be able to provide prompt and appropriate treatment.